Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

Mechanism of heterogeneous mixing between typical oxygenated volatile organic compound and hematite: implication for radiative forcing - Yongpeng Ji; Linghao Kong; Jiaxin Wang; Baocong Zhao; Zhiming Zhang; Shengping Chen; Sihao Lin; Jiangyao Chen; Yanpeng Gao; Yuemeng Ji (Atmospheric Environment, 2026)

Beyond conventional biochar: Sulfur-iron modification unlocks redox control for synergistic cadmium-arsenic sequestration in paddy soils - Zihao Liang; Hua Lin; Honghu Zeng; Sze-Mun Lam; Jin-Chung Sin; Xuehong Zhang; Guo Yu; Mi Feng; Yanpeng Liang; Huawei Li; Yuxi Lu; Gongning Chen (Environmental Research, 2026)

OH-initiated aqueous oxidation of methylglyoxal: Implications for organic acid and oligomer formation - Jiaxin Wang; Ying Chen; Wenjie Gao; Sihao Lin; Wenjian Li; Yongpeng Ji; Xiaolei Zhao; Yanpeng Gao; Yuemeng Ji; Taicheng An (Atmospheric Environment, 2026)

A modified stiffness matrix method based on precise integration method for free-field motion of layered transversely isotropic site - Yanpeng Li; Mingda Li; Zhiyuan Li; Zhigang Yin; Peijiang Cong; Gao Lin (Soil Dynamics and Earthquake Engineering, 2026)

Mid-late Holocene environmental change and social resilience in Central Plains of China: Evidence from Sha-Ying Rivers floodplain - Wei Li; YiHsien Lin; Linjing Liu; Xiaochen Pei; Ligang Zhou; Yanpeng Cao; Chen Liu; Hui Wang; Peng Lu; Yijie Zhuang; Meilin Guo; Fawei Liang; et al. (Quaternary Science Reviews, 2026)

A two-dimensional anionic covalent organic frameworks for ultra-efficient atmospheric water harvesting - Zhenhui Chen; Jingsong Feng; Yanpeng Cui; Daochuan Jiang; Yue Lin; Leyang Guo; Junjie Zhang; Yang Yang; Daolun Feng; Zhifu Liang (Chemical Engineering Journal, 2025)

Geophysical monitoring technology and simulation in CO2 geological storage: A comprehensive review - Wenke Tang; Wuqin Li; Zitian Lin; Jun Zhu; Siyao Zhou; Yangmin Kuang; Yanpeng Zheng (Gas Science and Engineering, 2025)

Synthesis of N-acyl-homoserine lactones analogs for improving the potential application of Acidithiobacillus thiooxidans in bioleaching - Deping Tang; Mengjiao Li; Wentao Song; Yanpeng Xi; Yali Liu; Yanyan Lin; Hao Feng; Aihong Mao (Archives of Microbiology, 2025)

Icing monitoring technology and application of 10 kV overhead distribution lines based on axial tension measurement - Lin Yang; Lulu Mei; Haochen He; Quan Liu; Yanpeng Hao; Licheng Li; Xinhao Lin (Cold Regions Science and Technology, 2025)

Electrical Resistivity Tomography Methods and Technical Research for Hydrate-Based Carbon Sequestration - Zitian Lin; Qia Wang; Shufan Li; Xingru Li; Jiajie Ye; Yidi Zhang; Haoning Ye; Yangmin Kuang; Yanpeng Zheng (Journal of Marine Science and Engineering, 2025)
This study focuses on the application of electrical resistivity tomography (ERT) for monitoring the growth process of CO2 hydrate in subsea carbon sequestration, aiming to provide technical support for the safety assessment of marine carbon storage. By designing single-target, dual-target, and multi-target hydrate samples, convolutional neural networks (CNNs), recurrent neural networks (RNNs), and residual neural networks (ResNets) were constructed and compared with traditional image reconstruction algorithms (e.g., back-projection) to quantitatively analyze ERT imaging accuracy. The experiments used boundary voltage as the input and internal conductivity distribution as the output, employing the relative image error (RIE) and image correlation coefficient (ICC) to evaluate algorithmic performance. The results demonstrate that neural network algorithms—particularly RNNs—exhibit superior performance compared to traditional image reconstruction methods due to their strong noise resistance and nonlinear mapping capabilities. These algorithms significantly improve the edge clarity in target identification, enabling the precise capture of the hydrate distribution during carbon sequestration. This advancement effectively enhances the monitoring capability of CO2 hydrate reservoir characteristics and provides reliable data support for the safety assessment of hydrate reservoirs.

Ultrahigh-efficiency and synchronous removal of microplastics-tetracycline composite pollutants via S-scheme core-shell magnetic nanosphere - Yujie Zhou; Xiaofeng Lin; Xin You; Ni Xue; Zilong Liu; Yanpeng Cai (Environmental Pollution, 2025)

Efficient and stable extraction of nano-sized plastic particles enabled by bio-inspired magnetic “robots” in water - Yanpeng Cai; Buyun Zheng; Xiaofeng Lin; Xin You; Qunpo Jia; Ni Xue (Environmental Pollution, 2025)

Distinct ultrafast dynamics of bilayer and trilayer nickelate superconductors regarding the density-wave-like transitions - Yidian Li; Yantao Cao; Liangyang Liu; Pai Peng; Hao Lin; Cuiying Pei; Mingxin Zhang; Heng Wu; Xian Du; Wenxuan Zhao; Kaiyi Zhai; Xuefeng Zhang; et al. (Science Bulletin, 2025)

Research status and prospects of CO2 geological sequestration technology from onshore to offshore: A review - Zitian Lin; Yangmin Kuang; Wuqin Li; Yanpeng Zheng (Earth-Science Reviews, 2024)

Ozone-delivering nanocomposite hydrogel for acute Staphylococcus aureus osteomyelitis treatment via neutrophil regulation - Hangtian Wu; Yihuang Lin; Yanpeng Lin; Mingye Deng; Jiahui Hou; Dahai Liu; Zhuang Cui; Daogang Guan; Jun Wang; Bin Yu (Chemical Engineering Journal, 2024)

Synergistic removal performance and mechanism of Cd(II) and As(III) from irrigation water by iron sulfide-based porous biochar - Yuxi Lu; Honghu Zeng; Hua Lin; Yanpeng Liang; Mi Feng; Zijian Zhou; Zihao Liang; Huawei Li; Gongning Chen (Environmental Science and Pollution Research, 2024)

Occurrence and bioaccumulation of parabens and their metabolites in the biota from a subtropical freshwater river ecosystem: Implications for human exposure - Yiling Lin; Yanan Zhao; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue (Environmental Research, 2024)

Simultaneous mitigating the bioavailability of cadmium and arsenic in paddy soil by two carbon-iron composites: A field-scale evaluation - Gongning Chen; Yuxi Lu; Mi Feng; Hua Lin; Yanpeng Liang; Zijian Zhou; Zihao Liang; Huawei Li; Honghu Zeng (Bioresource Technology Reports, 2023)

Berberine inhibits gluconeogenesis in spontaneous diabetic rats by regulating the AKT/MAPK/NO/cGMP/PKG signaling pathway - Ming Lu; Yanpeng Wang; Yuanye Jiang; Cuiping Zhang; Hongping Wang; Wenjun Sha; Lin Chen; Tao Lei; Limei Liu (Molecular and Cellular Biochemistry, 2023)

Torsional Optical Fiber Stress Analysis and Vortex-Induced Vibration Study of Three-Core Submarine Cable - Haotian Tan; Yanpeng Hao; Peng Zhang; Qishun Li; Wanxing Tian; Linhao Chen; Lin Yang; Licheng Li (Journal of Marine Science and Engineering, 2023)
Due to current scouring, submarine cables are prone to be exposed, suspended, and even vortex-induced vibration, which is not conducive to the safe operation of the power grid. In this contribution, the finite element simulation model of a 35 kV three-core optical fiber composite submarine cable with a suspended span length of 9.5 m is established. The natural frequency of the model is obtained through modal analysis. Then the vortex-induced vibration is simulated by the fluid–structure coupling method, and the stress distribution and change law of the torsional optical fiber is extracted. The results show that in the submarine cable, there appears to be a beating vibration and locking phenomena respectively, under two flow velocities. The transverse vibration amplitude of the latter increases significantly due to a resonance state. When the flow direction is perpendicular to the submarine cable, the stress distribution of the torsional optical fiber at the initial moment and at the 1/2 T moment of a vibration cycle approximately represents a mirror image relationship. In addition, the frequency of the stress change is the same as the frequency of the vortex-induced vibration, which can judge whether the vortex-induced vibration occurs. Moreover, the vortex-induced vibration range can be determined by the maximum stress change location.

Semi-analytical method for solving the anti-plane seismic dynamic response of steep slope site in a layered half-space - Yanpeng Li; Zhiyuan Li; Zhiqiang Hu; Gao Lin (Soil Dynamics and Earthquake Engineering, 2023)

Numerical Study of the Local Scouring Process and Influencing Factors of Semi-Exposed Submarine Cables - Qishun Li; Yanpeng Hao; Peng Zhang; Haotian Tan; Wanxing Tian; Linhao Chen; Lin Yang (Journal of Marine Science and Engineering, 2023)
Local scouring might result in the spanning of submarine cables, endangering their mechanical and electrical properties. In this contribution, a three-dimensional computational fluid dynamics simulation model is developed using FLOW-3D, and the scouring process of semi-exposed submarine cables is investigated. The effects of the sediment critical Shields number, sediment density, and ocean current velocity on local scouring are discussed, and variation rules for the submarine cables’ spanning time are provided. The results indicate that three scouring holes are formed around the submarine cables. The location of the bottom of the holes corresponds to that of the maximum shear velocity. The continuous development of scouring holes at the wake position leads to the spanning of the submarine cables. The increase in the sediment’s critical Shields number and sediment density, as well as the decrease in the ocean current velocity, will extend the time for maintaining the stability of the upstream scouring hole and retard the development velocity of the wake position and downstream scouring holes. The spanning time has a cubic relationship with the sediment’s critical Shields number, a linear relationship with the sediment density, and an exponential relationship with the ocean current velocity. In this paper, the local scouring process of semi-exposed submarine cables is studied, which provides a theoretical basis for the operation and maintenance of submarine cables.

Icing detection method of 500 kV overhead ground wire with tangent tower under special terrain based on vertical tension measurement technology - Lin Yang; Zhiqiang Chen; Yanpeng Hao; Hao Li; Zenghao Huang; Licheng Li (Cold Regions Science and Technology, 2023)

Desorption of CO2, SO2, and NH3 in the vacuum evaporation of desulfurization wastewater - Guifang Chen; Xiaofei Sun; Yunqi Feng; Zhanlong Song; Lin Cui; Yanpeng Mao; Chunyuan Ma; Shouyan Chen (Environmental Science and Pollution Research, 2021)